The Impact of Children's Interpersonal Communication with Parents and Parental Involvement in Fostering Independence of 3-4 Year Old Children - Ahsanty, Ratna; Imamah, Imamah (Journal of Childhood Development, 2024)
This study aims to examine the impact of interpersonal communication between children aged 3-4 years and parents and parental involvement in fostering children's independence. Independence is an important aspect in early childhood development, and is supported by warm, responsive communication patterns and active involvement of parents. This research uses a qualitative approach with a case study method on children aged 3-4 years at Tunas Harapan Ilahi Toddler School, Tangerang City. Data were collected through participatory observation, in-depth interviews with parents, and documentation. The results showed that effective communication between children and parents and involvement in daily activities have a positive impact on increasing children's independence. Children who received emotional support, opportunities to express their opinions, and were given small responsibilities showed better independence than children who lacked positive interactions. This conclusion reinforces the importance of interpersonal communication and parental involvement in shaping children's independent character from an early age. Based on these findings, it is recommended that parents and educators play an active role in building constructive communication and providing an environment that supports children's independence. This study contributes to the development of early childhood education programs that focus on independence.